Restricted repetitive behaviors in fragile X syndrome across the lifespan and the role of dynorphin and enkephalin within the basal ganglia - Sivayokan, Bhavana (My University, 2026)
Restricted repetitive patterns of behavior (RRBs) are varied and often disparate behaviors characterized by repetition, rigidity, invariance, and inappropriateness. These behaviors are transient and characteristic of normal development in infancy and childhood. However, they often persist in neurodevelopmental disorders such as autism spectrum disorder and fragile X syndrome, and manifest as symptoms of neurodegenerative diseases in old age. While RRBs have been linked with dysfunctional striatal circuitry, the changes in this circuitry and its role in the emergence of RRBs in fragile X syndrome are not clearly defined. Therefore, this study employed the Fmr1 knockout model of fragile X syndrome to assess repetitive behavior, its relationship with anxiety, and its association with the striatal neurotransmitters enkephalin and dynorphin. Male and female Fmr1 knockout and wildtype rats from two age groups underwent behavioral testing to assess RRBs and anxiety-related behavior, following which a subset of animals was euthanized, and their striatum was collected for quantification of dynorphin and enkephalin. In general, increased RRBs were observed among knockout animals than among wildtype animals with different forms of RRBs being prominent at each timepoint. Furthermore, RRBs showed significant associations with enkephalin and dynorphin levels but not anxiety. RRBs increased significantly with increasing dynorphin to enkephalin ratio among old animals, and with decreasing enkephalin levels in young animals and old wildtype but not knockout animals. These findings suggest that striatal enkephalin and dynorphin signaling show age-related changes and are involved in the emergence of RRBs in fragile X syndrome. The regulation of these neurotransmitter levels in the striatum could help reduce RRBs.
Keywords: Repetitive behavior; Neurodevelopmental disorders